Axonal swellings and spheroids: a new insight into the pathology of neurocysticercosis. (11th December 2018) - Mejia Maza, Alan; Carmen‐Orozco, Rogger P.; Carter, Emma C; Dávila‐Villacorta, Danitza G.; Castillo, Gino; Morales, Jemina D.; Mamani, Javier; Gavídia, Cesar M; Alroy, Joseph; Sterling, Charles R.; Gonzalez, Armando E.; García, Héctor H.; et al.
Abstract: Neurocysticercosis is a parasitic brain disease caused by the larval form (Cysticercus cellulosae) of Taenia solium and is the leading cause of preventable epilepsy worldwide. However, the pathophysiology and relation to the wide range of clinical features remains poorly understood. Axonal swelling is emerging as an important early pathological finding in multiple neurodegenerative diseases and as a cause of brain injury, but has not been well described in neurocysticercosis. Histological analysis was performed on human, rat and porcine NCC brain specimens to identify axonal pathology. Rat infection was successfully carried out via two routes of inoculation: direct intracranial injection and oral feeding. Extensive axonal swellings, in the form of spheroids, were observed in both humans and rats and to a lesser extent in pigs with NCC. Spheroids demonstrated increased immunoreactivity to amyloid precursor protein and neurofilament indicating probable impairment of axonal transport. These novel findings demonstrate that spheroids are present in NCC which is conserved across species. Not only is this an important contribution toward understanding the pathogenesis of NCC, but it also provides a model to analyze the association of spheroids with specific clinical features and to investigate the reversibility of spheroid formation with antihelminthic treatment.